Dampak Deklarasi Bersama Indonesia Dan Jerman Di Bidang Kesehatan Terhadap Tenaga Kesehatan Indonesia - Djoesept Harmat Tarigan (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The main problem discussed in this study is how the impact of the joint declaration between Indonesia and Germany in the health sector has on Indonesian health workers. The research method used is a qualitative research method. Where this research will use two data collection techniques, namely literature research and interviews, both structured and semi-structured. The results of this study have seen that the impact of the joint declaration between Indonesia and Germany in the health sector will certainly provide excess benefits and advantages for Indonesian health workers who want to work in Germany. Indonesian health workers who want to work in Germany will certainly have a high income and can use it for personal or family interests. Indonesian health workers can also add to their insights because living in a developed country will certainly be different from Indonesia, which is a developing country